Embolization of the superior rectal arteries for chronic bleeding due to haemorrhoidal disease. (February 2017) - Moussa, N.; Sielezneff, I.; Sapoval, M.; Tradi, F.; Del Giudice, C.; Fathallah, N.; Pellerin, O.; Amouyal, G.; Pereira, H.; de Parades, V.; Vidal, V.
Abstract: Aim: The aim of this study was to assess the safety and efficacy of the emborrhoid technique (embolization of the superior haemorrhoidal arteries) in patients ineligible for surgery. Methods: Between January 2014 and April 2015, 30 consecutive patients (average age 58 years) suffering from disabling chronic bleeding due to haemorrhoidal disease and with a contraindication for surgery ( n = 23) or with a failure of instrumental or surgical treatment ( n = 7) underwent embolization. All cases were discussed at multidisciplinary meetings including a proctology specialist or a surgeon and an interventional radiologist. We performed super selective micro coil embolization (pushable 2–3 mm fibre coils) of the distal branches of the superior rectal arteries with a microcatheter, via a right femoral approach, under local anaesthesia. We assessed clinical outcome by evaluating bleeding and specific clinical scores relating to bleeding and changes in quality of life. Results: Immediate technical success, with no complication, was achieved in 93% of cases. A mean of 3.1 arteries per patient was embolized, with a mean of 7.6 coils per patient. Median follow‐up was 5 months. Clinical score improvement was observed in 72%, in 17 patients after a single embolization session, and in four additional patients after a second embolization session. No improvement in bleeding was observed in eight patients (28%). Conclusion: Distal coil embolization of the superior rectal arteries for disabling chronic bleeding due to haemorrhoidal disease is safe and effective in patients untreatable by surgery.